Corporate Social Responsibility (CSR) and Entrepreneurship: A Conceptual Model - Wong, Teik Aun; Bustami, Mohammad Reevany; Ong, Tze Chin*; Ow Yong, Mun Geet (INTI International University, 2020)
Corporate Social Responsibility (CSR) is growing in prominence and importance. Large businesses such as banks are instituting comprehensive CSR programs that focus on social and environment concerns. Concurrently, the interest in entrepreneurship is also growing. Entrepreneurship fosters economic growth, social development, creates jobs and encourages innovation. Thus far, in the Malaysian context, these two phenomena are developing largely in isolation. CSR programs that focus on assisting entrepreneurs are absent. Herein lies an opportunity to synergize and create value. Large businesses, particularly banks, are wellpositioned to assist entrepreneurs gain a foothold in the business world. Banks have the management expertise, credit facilities and business networks to assist entrepreneurs in an effective and efficient manner. An overview of neighboring Indonesia reveals several banks deploying CSR programs that specifically assists entrepreneurs. Institutional Isomorphism Theory is used to frame and conceptualize this phenomenon. Data collection methodology is document analysis in a cross-country comparative context. The findings suggest isomorphic tendency and suitability for Malaysian banks to emulate their Indonesian brethren in instituting CSR programs tailored to assist entrepreneurs. Specifically, a CSR program targeted at entrepreneurs in Malaysian night markets is proposed. The proposed CSR program assists this targeted group to embrace e-commerce, finance business development and adopt other modern business practices. Conceptually, this proposed CSR program can actualize an “enhanced night market” that is commercially competitive, socially sustainable and can potentially become international tourist attractions.